Women in crime - Nadia Campaniello (IZA World of Labor, 2014)
In recent decades, womenâs participation in the labor market has increased considerably in most countries and is converging toward the participation rate of men. Though on a lesser scale, a similar movement toward gender convergence seems to be occurring in the criminal world, though many more men than women still engage in criminal activity. Technological progress and social norms have freed women from the home, increasing their participation in both the labor market and the crime market. With crime no longer just menâs business, it is important to investigate female criminal behavior to determine whether the policy prescriptions to reduce crime should differ for women.
Keywords: J16; K00; 330; crime; women; gender gaps